Сurrent state of clinical significance of early kidney injury markers - D. N. Khotko; A. I. Khotko; A. I. Tarasenko; A. O. Efimova (Исследования и практика в медицине, 2022)
Study objective was to reflect the current state of the early kidney damage markers clinical significance in patients with urolithiasis. Authors performed a literature review of articles (original studies and reviews) published between 2018 and February 2022 on the study of pro‑inflammatory, profibrotic and angiogenic factors in urolithiasis. Bibliographic, informational and semantic source search methods in Google Scholar, PubMed, Scopus and Embase databases were used. Analysis of a legalistic and systematic sources was carried out.Proteinuria, serum creatinine and glomerular filtration rate are now accepted as the main diagnostic markers of renal lesions. These markers already allow to reveal lesions at the stage of chronic kidney disease, when the lesion process is practically irreversible. Today it is most relevant to conduct the search for biomarkers of acute and chronic renal lesions at patients with urolithiasis to detect pathological changes in the kidneys and to determine their nature at an early stage of diagnosis.Improved diagnostic techniques destined to provide a detailed picture of the development of the pathological process in patients with urolithiasis will make it possible to prevent renal failure development at an early stage in this category of patients.